Tecnologia assistiva para promoção do envelhecimento ativo segundo profissionais e idosos participantes de grupo de convivências. - Leite, Eliane de Sousa (2016)
assistive technology is still a recent term, in Brazil, which aims to use a range of resources and services that contribute to provide or expand functional abilities of people with disabilities and/or elderly, thus, promoting active aging with quality of life, independence and social inclusion. Objective: Check the knowledge produced in the scientific literature about the contributions of assistive technology to maintain the functionality of the older person; Identify the importance of the use of assistive technology for active ageing, according to professionals who work in living groups; • Meet the conceptions about assistive technology and his contributions to the active aging for older people. Method: exploratory research with mixed approach, carried out in the three living groups for the elderly in the city of Cajazeiras, Paraíba. The sample studied consisted of 45 professionals and 172 elderly. Data collecting was performed with professionals and elderly, between March and December 2014, through interviews with semi-structured guide, containing demographic data and issues related to the theme. For the analysis of empirical data the Iramuteq Software was used to process the data, and Content Analysis Technique proposed by Bardin to support analysis. The social-demographic data of the subjects were tabulated and analyzed using the Statistical Package for Social Sciences Software, version 22.0. The study attended the ethical and legal guidelines, inherent to the research protocol involving human subjects, contained in Resolution No. 466/12, with protocol number 652.809/2013. Results: three articles presented in the results and discussion section. The first was published; the second one, submitted for publication; and the third one will be defense object. One enhanced, by the results of this research, the importance of Assistive Technology for increasing functionality, autonomy, social integration and consequently a better quality of life. The professionals recognize this resource as vital for the improvement of their daily practices and critical to a more appropriate care for the elderly. Some of the surveyed professionals know and use the service in their working practice; others reported lack of theoretical knowledge and skill for this purpose. Regarding the elderly, they do not recognize the instrument and identify it as something relevant to health, but do not know the difference between the overall technology from the assistive one. Conclusion: it is understood that the Assistive Technology is a feature that allows the elderly to develop the functional activities of daily life safely, increase their independence and autonomy, and prevent comorbidities. Thus, it is necessary to raise awareness among professionals and researchers about the benefits that the use of Assistive Technology can bring to the elderly, providing their social inclusion, the conquest and the practice of citizenship. In this sense the Assistive Technology is an important tool that should be considered to improve the health of the elderly.